الصحراء في العتبات, رواية الطرحان لعبد الله كروم أنموذجا قراءة سيميائية - صالحي, حسينة; قعر المثر, النعيم (جامعة الوادي - University of Eloued, 2023)
ملخص: ازداد الاهتمام في الآونة الأخيرة برواية الصحراء على الساحة الأدبية والنقدية, حيث أصبحت الهامش الذي يسعى لزحزحة مركزية المدينة, وتيمة سردية تحمل مسؤولية بعث الجَمال من تحت الكثبان الرملية إلى القارئ الذي اقترنت صورة الصحراء لديه بالخلاء والخراب والعطش, فظهرت روايات تصور الصحراء فضاء استعاريا يحمل بين كثبانه ذاكرة المكان والزمان والانسان, وتسعى هذه الدراسة إلى تقصي مظاهر الصحراء وكيفية ظهورها من خلال العتبات النصية في رواية الطرحان لعبد الله كروم, وذلك في دراسة سيميائية تُفكك دلالة هذه العتبات وتستنطقها كونها نصوصا موازية للمتن تحاور أفق توقع القارئ وتغويه, فهي علامات لغوية ورموز تُشكل الخطاب الروائي وتحدد هويته وتجذب المتلقي لتفكيك تمفصلاته للوصول إلى كُنهه انطلاقا من أن كل شيء في العمل الأدبي له دلالة تعين على فهم المتن السردي, ومن هذا المنطلق كيف وُظِّفت الصّحراء في العَتبات؟ وإلى أي مدى حملت دلالات المتن؟. الكلمات المفتاحية: العتبات النصية ـــــــــ السيمياء ــــــ رواية الصحراء ـــــــــ صورة الغلاف ــــــ العنوان ــــــــ العناوين الداخلية. Abstract: Interest in the desert novel has recently increased in the literary and critical arena, as it has become the margin that seeks to displace the centrality of the city, and a narrative theme that bears the responsibility of sending beauty from under the sand dunes to the reader whose image of the desert was associated with emptiness, desolation, and thirst. Novels then appeared depicting the desert as an allegorical space that carries between its dunes the memory of place, time and man. This study seeks to investigate the manifestations of the desert and how they appear through the textual thresholds in the novel Al-Tarhan by Abdullah Karroum, in a semiotic study that deconstructs the significance of these thresholds and interrogates them as being texts that are parallel to the text bodywhich dialogue with the horizon of the reader’s expectation and seduction, as they are linguistic signs and symbols that form the narrative discourse and define its identity. They are linguistic signs and symbols that make up the narrative discourse and define its identity, and attract the recipient to dismantle its articulations to reach its essence, based on the fact that everything in the literary work has a sign that helps to understand the narrative body, and from this standpoint, these questions are formulated. How was the desert employed in the thresholds? To what extent did it carry the semantics of the text? Key words: Text Thresholds , Semiotics , Desert Novel , Cover Image , Title , Internal Titles.
Keywords: لعتبات النصية ـــــــــ السيمياء ــــــ رواية الصحراء ـــــــــ صورة الغلاف ــــــ العنوان ــــــــ العناوين الداخلية. ;; Key words: Text Thresholds , Semiotics , Desert Novel , Cover Image , Title